Sexual act as a psychological counter to self-assertion in the novel Al-Khubz Al-Hafi by Muhammad Shukri (writing taboos and breaking the taboo) - Ali saoucha, Souheyla; Benlokrichi, Ammar (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
In this article. talked about talking about experimentation as a retrofit operating mechanism in the narrative text. through the delinquency of writing about taboos (breaking the maharram (and exhuming its mysteries and delving into it as a kind of ipermeable aspect of sex and linking it with its psychological rootedness that represented the florr of furnishing for this type of writing as it considered self-crises creativity is the main pillar of the act . and this is proven by research on this topic. as it represented the polarized experimentation of the creator after he found in it all the possibilities of writing capable of absorbing psychological disttress and the crisis caused by economic. social. and political changes. by relying on new operating mechanisms that gave the novel flexibility to cope with these changes. The new writing also represented a door that opened up to the struggle in exploring its practices that are hidden under the moral charter. such as touching forbidden through writing about sex. for example. as well as the conversation and exposing all the excesses that take place in the right of the self and which is aggravated by the act of its existence. and this is what the study produced by analyzing and describing the extrapolated model .that tis using the descriptive analytica method The influence of internal factors, and accordingly, the factors affecting the influence of internal factors differ from other factors that affect one other influence in their effect, due to their influence in contributing to one contribution, instead, these factors differ one effect to another according to the severity The mental and psychological aspect, and printing influences the personality under this circumstance, to produce after that a reaction that is often out of the ordinary and unpleasant in our society, which is under the imposition of customs, traditions, religion, etc. Exist for what exists, bears psychological distress for the character